Generalized Edema and Pseudothrombocytopenia After ChAdOx1 nCoV-19 COVID-19 Vaccination: A Case Report - Bokel, Joanna; Mendes-de-Almeida, Daniela P.; Martins-Gonçalves, Remy; Palhinha, Lohanna; Vizzoni, Alexandre G.; Correa, Danusa Ferreira; Brandão, Luciana Gomes Pedro; Bozza, Patrícia T.; Grinsztejn, Beatriz (Frontiers in Public Health, 2022)
Reports of side effects of vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are increasing worldwide. Capillary leak syndrome and vaccine-induced immune thrombotic thrombocytopenia are very rare but life-threatening adverse events that should be identified early and treated. However, isolated thrombocytopenia can indicate pseudothrombocytopenia. In certain people, ethylenediaminetetraacetic acid (EDTA) induces an in vitro platelet aggregation, resulting in misleading underestimation of platelet counts. It is essential to recognize pseudothrombocytopenia to prevent diagnostic errors, overtreatment, anxiety, and unnecessary invasive procedures. We present a case who developed generalized edema and persistent pseudothrombocytopenia after the first dose of the ChAdOx1 nCoV-19 vaccine.